Population attributable fractions of depression and anxiety among Aboriginal and Torres Strait Islander peoples: a population-based studyResearch in context - Subash Thapa; Kedir Y. Ahmed; Santosh Giri; Anayochukwu E. Anyasodor; M. Mamun Huda; Peter Gibbs; Shakeel Mahmood; Feleke H. Astawesegn; Jamie Newman; Allen G. Ross (Elsevier, 2024)
Summary: Background: Aboriginal and Torres Strait Islander peoples face an increased risk of common mental disorders, which may be associated with underlying socio-economic challenges, racism, and discrimination. This is the first study to calculate the population attributable fractions (PAFs) for depression and anxiety attributed to potentially modifiable risk factors such as health behaviour, social and cultural characteristics, and past adverse events among Aboriginal and Torres Strait Islander peoples aged ≥15 years. Methods: This cross-sectional study examined the 2018-19 National Aboriginal and Torres Strait Islander Health Survey conducted by the Australian Bureau of Statistics. Logistic regression models were used to compute odds ratios (ORs). PAFs adjusted for communality were calculated using adjusted ORs and prevalence estimates for each risk factor. Findings: This study included a weighted sample of 5362 individuals, with a mean age of 40.8 years (SD = ±17.2). Personal income below the national average (PAF = 13.4%; 95% CI: 12.4, 14.5), severed access to Indigenous cultural affiliations (PAF = 12.8%; 95% CI: 11.8, 13.8), central obesity (PAF = 7.2%; 95% CI: 6.4, 8.0), daily smoking (PAF = 5.9%; 95% CI: 5.2, 6.7) and severed access to Indigenous knowledge (PAF = 5.2%; 95% CI: 4.5, 5.8) were associated with 45% of depression cases. Personal income below the national average (PAF = 10.7%; 95% CI: 9.8, 11.7), limited access to Aboriginal Community Controlled Health Services (PAF = 10.6%; 95% CI: 9.7, 11.6), central obesity (PAF = 7.1%; 95% CI: 6.3, 7.9), severed access to Indigenous knowledge (PAF = 5.7%; 95% CI: 4.9, 6.4) and the experience of discrimination in the last 12 months (PAF = 4.7%; 95% CI: 4.0, 5.3) were associated with 39% of anxiety cases. Interpretation: To reduce the burden of depression and anxiety disorder among Aboriginal and Torres Strait Islander peoples, addressing socio-economic and cultural harms that constrain healthy connections to people/kin, their rights, languages, land, and healthy food sources should be a priority. Funding: This work was funded by a grant from the Commonwealth of Australia, represented by the Department of Health and Aged Care (Grant Activity 4-DGEJZ1O/4-CW7UT14).